Looks or performance? How physical education teachers’ body shape and physical appearance shape student motivation - Mohamad Nizam Nazarudin; Zakiah Noordin (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study examines the correlation between the body shape and physical appearance of physical education (PE) teachers and the motivation of secondary school students in PE classes in Malaysia. Using a correlational research design, the study sampled 590 students aged 15-18 from urban, suburban, and rural secondary schools in Malaysia. Data collection was facilitated through a self-developed questionnaire: Physical Education Teacher Body Shape (PETBS), Physical Education Teacher Physical Appearance (PEPA), and Physical Education Intrinsic and Extrinsic Motivation (PEIEM). The scales Cronbach’s alpha values are between 0.850 and 0.929. Descriptive statistics, T-tests, and Pearson’s correlation analyses were performed using SPSS version 29. The results indicated significant differences in students’ perceptions of their PE teachers’ body shape and appearance and students’ motivation varied by school type. Perceptions at urban schools were signifi cantly lower than those in suburban and rural schools, with suburban schools signifi cantly lower than rural schools. There were strong positive correlations between the teachers’ body shape (r = 0.952) and appearance (r = 0.935) and the student’s motivation in PE classes. These findings underscore the significant influence of PE teachers’ physical characteristics on student motivation, highlighting the importance of considering these attributes in teacher recruitment and professional development. Future research should consider employing experimental and longitudinal study designs, as well as mixed-methods approaches, to further investigate their implications for educational practices.